Analysis of Challenges and Barriers in the Implementation of Standard Inpatient Wards at Hospital - Putra Harahap, Bahdi Mandala; Balqis Wasliati; Tati Murni Karo Karo (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: RSU Wira Husada Kisaran faces challenges in implementing the Standard Inpatient Class (KRIS) in accordance with the applicable regulations. Despite planning efforts, obstacles such as the absence of a formal organizational structure, uneven distribution of medical personnel, and limited funding continue to hinder KRIS implementation. Research Objective: This study aims to analyze the current implementation of KRIS at RSU Wira Husada Kisaran, identify the existing obstacles, and explore policy alternatives to improve the incident reporting system for patient safety and the overall KRIS implementation.Research Method: This research employs a qualitative approach with Grounded Theory to uncover the factors that hinder KRIS implementation. Data was collected through interviews with hospital management, medical staff, and nursing personnel. To develop alternative policies, the study used the Analytical Hierarchy Process (AHP). Results: The results show that while the hospital has developed a KRIS plan, challenges such as uneven distribution of nurses, slow funding management, and the absence of a specific SOP for KRIS persist. The facilities and infrastructure meet most standards; however, maintenance and facility improvements still need to be enhanced. Conclusion:RSU Wira Husada Kisaran has taken steps to overcome these obstacles. However, strengthening the formal organizational structure, maintenance systems, and transparency in financial management are still necessary to improve the effectiveness of KRIS.